GPRS : gateway to third generation mobile networks - Heine, Gunnar; Sagkob, Holger (Boston, MA : Artech House, 2003)
This innovative new book, from leading industry experts Gunnar Heine and Holger Sagkob, puts a focus on GPRS (General Packet Radio Service) but also explains the alternative and complementary technologies HSCSD, EDGE, IS-136 HS. It teaches you how the packet data standard GPRS can help you to expand your network towards third generation, meeting the demands of the most-sophisticated mobile data applications. The book focuses on the specifics and procedures of the air-interface, while giving you a thorough understanding of IP related protocols and a detailed presentation of all the important protocol scenarios that you may encounter in GPRS and HSCSD. Other discussions include an introduction to GSM and TDMA, data transmission protocols, and terrestrial interfaces. An extensive glossary provides answers to many of the technical questions that may arise while utilizing GPRS, HSCSD, EDGE or IS-136 HS technology. Packed with more than 200 illustrations that support key topics.
1. The Basics: Principles of GSM and Influences on GPRS -- 2. Introduction to GPRS -- 3. The Air Interface in GPRS -- 4. QoS, Mobility, and Session Management in GPRS -- 5. The GPRS Protocol Stack -- 6. Introduction to HSCSD.
Print version record.
Includes bibliographical references and index.
Added to collection customer.56279.3
Keywords: Mobile computing; Mobile communication systems; Informatique mobile; Radiocommunications mobiles; COMPUTERS -- Networking -- Vendor Specific; COMPUTERS -- Data Transmission Systems -- General; Mobile communication systems; Mobile computing